IMPROVING THE VOCABULARY MASTERY THROUGH NUMBERED HEADS TOGETHER TECHNIQUE OF THE SEVENTH GRADE STUDENTS OF SMP N 5 BATURITI IN ACADEMIC YEARS 2015/2016 - ., I Dewa Made Adhi Wira Sanjaya; ., Dr.Sudirman, M.L.S; ., Nyoman Karina Wedhanti, S.Pd., M.Pd (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
Penelitian ini merupakan penelitian tindakan berdasarkan kelas yang bertujuan: (1) untuk mengetahui apakah Numbered Heads Together teknik dapat meningkatkan siswa penguasaan kosakata, (2) untuk mengetahui respon siswa terhadap pelaksanaan strategi. Penelitian ini dilakukan dalam dua siklus yang terdiri dari tiga sesi pada setiap siklus. Ada dua jenis data (kualitatif dan data kuantitatif) yang dikumpulkan melalui tes, kuesioner, dan buku harian penulis. Hasil tes menunjukkan bahwa penguasaan kosakata ditingkatkan pada setiap siklus. skor rata-rata siswa adalah 4,63% di pre test, 6.2 di post test 1, dan peningkatan menjadi 7.97 di post test 2. Hal ini dapat juga dilihat pada jumlah siswa lulus ujian. Tidak ada siswa lulus dalam pre test, 2 siswa dalam post test 1, dan 18 siswa di post test 2. Hasil diary penulis dan kuesioner juga menunjukkan bahwa siswa memberikan respon positif terhadap strategi. Hasil kuesioner menunjukkan bahwa 18 (90%) dari siswa mengakui bahwa mereka benar-benar seperti pelaksanaan Numbered Heads Together teknik. Selain itu, 17 (85%) dari siswa mengaku bahwa mereka termotivasi dalam belajar bahasa Inggris menggunakan Numbered Heads Together teknik Kata Kunci : Numbered Heads Together teknik, Penguasaan kosa kata This study was a classroom based action research which aimed: (1) to find out whether Numbered Heads Together technique can improve students’ vocabulary mastery, (2)to find out the response of the students toward the implementation of the strategies. This study was conducted in two cycles consisting of three sessions in each cycle. There were two kinds of data (qualitative and quantitative data) which were collected through tests, questionnaire, and writer’s diary. The result of the tests showed that the students’ vocabulary mastery was improved in each cycle. The students’ mean score was 4.63% in pre test, 6.2 in post test 1, and improved became 7.97 in post test 2. It can be also seen on the number of students passing the test. There were no students passed in the pre test, 2 students in the post test 1, and 18 students in the post test 2. The result of writer’s diary and questionnaire also showed that the students gave positive response toward the strategies. The results of the questionnaires showed that 18 (90%) of the students admitted that they really like the implementation of Numbered Heads Together technique. Moreover, 17 (85%) of the students admitted that they were motivated in learning English using Numbered Heads Together technique. keyword : Numbered Heads Together Technique, Vocabulary Mastery